Multi Server Collaborative Auditing in Encrypted Data Storage with Blockchain Technology - V. Archana. M.E.,; G. Saraswathi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Traditional centralized cloud storage systems often face vulnerabilities such as single points of failure, data breaches, and unauthorized access. To address these challenges, this study proposes a blockchain-based approach for secure data storage on the cloud while providing controlled data access. The proposed system leverages the decentralized and immutable nature of blockchain to ensure the integrity and security of stored data. Blockchain technology, known for its decentralized and immutable nature, can enhance the security and transparency of data storage. In this proposed approach, data is encrypted and distributed across multiple nodes in the cloud, eliminating the risk of a single point of failure. The data is then recorded as a series of tamper-proof blocks on a blockchain, ensuring data integrity and preventing unauthorized modifications. Each block includes a hash pointer that links it to the previous block, creating a chain of blocks that forms the blockchain. To ensure data integrity, Third-Party Auditors (TPAs) are introduced. These independent entities perform regular audits on the stored data and verify its integrity against the hashes stored on the blockchain. The TPAs act as trusted entities that ensure the accuracy and consistency of the data, reducing the reliance on the data storage provider. The proposed system enhances the security of data storage by eliminating single points of failure and preventing unauthorized modifications. By leveraging the decentralized and transparent nature of blockchain technology, this approach addresses the limitations of traditional cloud storage systems, providing enhanced security, data integrity, and controlled data access. The proposed system has the potential to revolutionize data storage practices and contribute to the development of more secure and trustworthy cloud storage infrastructures.
Keywords: Cloud Framework; User Enrolment; Data Encryption; Data Block Creation; Data Auditing